Moral Compliance and the Concealed Charm of Prudence - Tullberg, Jan (Journal of business ethics, 2009)
The key to moral behavior is often perceived to consist of ignoring rational self-interest and instead following norms recommended by religious tradition and moral philosophy. A central issue is the connection between these ambitions and actual behavior. Are an idealistic mood and an ethics of ambition the way out of an iron cage of individualistic rational behavior? Or is ethics best served by rules and incitements in harmony with rationality? The article discusses morality from the perspective of compliance. A normative suggestion in the Prisoner’s Dilemma exemplifies the case of prudent morality. The player should contribute if the expected value of that choice exceeds his payoff of mutual defection. The article questions the value of an absolute morality and suggests a morality that is more of a prudent policy than a categorical imperative. A conviction favoring a good average result in the long run is the most relevant argument for complying with a rule. The structure of economic games can give useful insights about problematic situations and consequences of different strategies. Being prudent rather than doing good might be a better policy not only for the agent, but also for organizations and society.